Comparison of effectiveness, cost and safety between moderate sedation and deep sedation under esophagogastroduodenoscopy in Chinese population: a quasi-experimental study. (2nd September 2022) - Hu, Feng; Zou, Long; Chang, Hongxia; Tian, Lin; Liu, Fanrong; Lan, Ya; Zhang, Fangxin; Liu, Xiao
Abstract: Objective: Most endoscopists routinely perform moderate or deep sedation for esophagogastroduodenoscopy (EGD). Considering that there is no consensus on the optimal sedation depth and it varies from country to country, our study aims to compare the effectiveness, cost and safety of these two sedation methods in the Chinese population. Methods: This quasi-experimental study included a total of 556 eligible patients from July 2020 to June 2021, and they entered the moderate sedation group or deep sedation group based on their choices. Baseline information, scores of Patient Satisfaction with Sedation Instrument (PSSI) and Clinician Satisfaction with Sedation Instrument (CSSI), examination time, sedation time, recovery time, expenses before medicare reimbursement, hypoxaemia and hypotension were compared between the two groups. Propensity Score Matching (PSM) analysis was conducted to balance the confounding factors. Results: After PSM, 470 patients were involved in the analysis, with 235 for each group. The moderate sedation was clearly superior to the deep sedation group in terms of PSSI score (98.00 ± 0.94 vs. 97.29 ± 1.26), CSSI score (98.00 ± 0.78 vs. 97.67 ± 1.30), sedation time (11.90 ± 2.04 min vs. 13.21 ± 2.75 min), recovery time (25.40 ± 3.77 min vs. 28.0 ± 4.85 min), expenses (433.04 ± 0.00 Yuan vs. 789.85 ± 0.21 Yuan), with all p  < .001. Examination time was not significantly different between the two groups ( p  = .124). In addition, the moderate sedation group had a lower occurrence rate of hypoxaemia (0.36% vs. 3.27%, p  = .010) and hypotension (17.44% vs. 44.00%, p  < .001) compared to the deep sedation group. Conclusions: Moderate sedation presented better effectiveness and safety and lower cost, and thereby it should be recommended as a widely used sedation method in clinical practice in China. Trial registration: This trial was registered on http://www.chictr.org.cn/index.aspx (ChiCTR2000038050).